PENERAPAN ALGORITMA GREEDY DALAM MENENTUKAN MINIMUM SPANNING TREES PADA OPTIMISASI JARINGAN LISTRIK JALA - Didiharyono Didiharyono; Siti Soraya (Jurnal Varian, 2018)
This article discusses the applied of greedy algorithm principle in finding the optimum solution in determine minimum spanning tree on graph. Graph theory is one of the studies in discrete mathematics that are widely applied in various scope. This article is a literature study and applied of nets electricity network optimization using Prims algorithm and Kruskal algorithm. Network Nets System is one type of electrical network system construction. Based on results of the study and discussion can be concluded that the application of greedy algorithm using Prims algorithm and Kruskal algorithm in determine minimum spanning tree on its principle is the same. However, after a comparison between the two algorithms we consider that the ideal algorithm used to optimize the nets electric network is the Kruskal algorithm because in the case of the electric network has few sides and many vertices.